2017
DOI: 10.1016/j.jtho.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Combination Osimertinib and Gefitinib in C797S and T790M EGFR-Mutated Non–Small Cell Lung Cancer

Abstract: This is, to the best of our knowledge, the first reported case of combination EGFR tyrosine kinase inhibitor therapy tailored to the allelic conformation of T790M and C797S mutation that resulted in brief clinical improvement without toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
132
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(133 citation statements)
references
References 16 publications
1
132
0
Order By: Relevance
“…Till now, limited studies reported the resistant mechanism of osimertinib and extreme complicated resistant profiles were identified based on current data [49][50][51]. Fortunately, several preclinical and small size studies have provided potential treatment modalities to overcome the resistance, but an umbrella trial should be designed to address the pending issues [48,[52][53][54][55][56][57][58][59][60][61][62][63]. On the other hand, considering the rapid development of checkpoint inhibitors (CPIs) in advanced NSCLC, whether CPIs could benefit in patients with pan-negative oncogenes after osimertinib or treatment failure of novel combination modality remained to be explored in prospective trials.…”
Section: Osimertinib (Azd9291)mentioning
confidence: 99%
“…Till now, limited studies reported the resistant mechanism of osimertinib and extreme complicated resistant profiles were identified based on current data [49][50][51]. Fortunately, several preclinical and small size studies have provided potential treatment modalities to overcome the resistance, but an umbrella trial should be designed to address the pending issues [48,[52][53][54][55][56][57][58][59][60][61][62][63]. On the other hand, considering the rapid development of checkpoint inhibitors (CPIs) in advanced NSCLC, whether CPIs could benefit in patients with pan-negative oncogenes after osimertinib or treatment failure of novel combination modality remained to be explored in prospective trials.…”
Section: Osimertinib (Azd9291)mentioning
confidence: 99%
“…4 Identification of NSCLC patients likely to profit from these novel therapies relies on the detection of specific biomarkers in tumor biopsies. 5 Further targets, including SSH and ERBB3 in NSCLC are under investigation, [11][12][13] and novel molecular resistance mechanisms, such as EGFR C797S in case of thirdgeneration EGFR TKI, 14 are continuously being discovered, requiring expeditious adaptability of testing approaches to supply clinically relevant genetic information to medical oncologists. In addition, patients with a pulmonary squamous cell carcinoma (SCC) and high clinical suspicion for actionable mutations, based for example on a never-or light-smoking history and/or young age, should be offered molecular testing as well.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of EGFR, ALK 9 and ROS1 10 is mandatory, and the inclusion of additional drug targets, such as BRAF, MET, RET, ERBB2 (HER2), as well as additonal markers, like KRAS, is recommended. 5 Further targets, including SSH and ERBB3 in NSCLC are under investigation, [11][12][13] and novel molecular resistance mechanisms, such as EGFR C797S in case of thirdgeneration EGFR TKI, 14 are continuously being discovered, requiring expeditious adaptability of testing approaches to supply clinically relevant genetic information to medical oncologists.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the current reporting practices for NGS‐based ctDNA analysis and to assess the reporting consistency between different laboratories, a set of simulated ctDNA samples and a corresponding case scenario were distributed to genetic testing laboratories for ctDNA analysis. The sample design and corresponding clinical information originated from recently published case reports . Four commonly detected and clinically relevant variants in the EGFR and TP53 genes, with variant allelic frequencies (VAF) ranging from 0.1% to 10%, were incorporated into our panel.…”
Section: Methodsmentioning
confidence: 99%